Hardy-type inequality for 0<p<1 and hypodecreasing functions - Burenkov, Victor; Tararykova, Tamara; Senouci, Abdelkader (Eurasian Mathematical Journal, 2010)
The notion of a hypodecreasing function is introduced. Some properties of hypodecreasing functions are proved and several examples are given. It is established that the Hardy-type inequality for Lp-spaces with 0 < p < 1 is satisfied for some spaces of hypodecreasing functions. The obtained result is in a certain sense sharp.